2017
DOI: 10.1093/rheumatology/kex269
|View full text |Cite
|
Sign up to set email alerts
|

52-week results of the phase 3 randomized study comparing SB4 with reference etanercept in patients with active rheumatoid arthritis

Abstract: ObjectiveTo compare the 52-week efficacy and safety of SB4 [an etanercept biosimilar] with reference etanercept (ETN) in patients with active RA.MethodsIn a phase 3, randomized, double-blind, multicentre study, patients with moderate to severe RA despite MTX treatment were randomized to receive 50 mg/week of s.c. SB4 or ETN up to week 52. Efficacy assessments included ACR response rates, 28-joint DAS, Simplified and Clinical Disease Activity Indices and changes in the modified total Sharp score (mTSS). Safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
70
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 26 publications
5
70
0
2
Order By: Relevance
“…TNF-α is wellestablished in arthritis, and anti-TNF agents have been extensively studied for therapy of inflammatory arthritis as well as osteoarthritis [18,19]. TNF-α enhances expression of MMPs and ADAMTS [8,20,21], and these increased proteases in turn cause exaggerated degradation of cartilage matrix including cartilage oligomeric matrix protein, Col II, and Aggrecan, which promotes progression of OA [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is wellestablished in arthritis, and anti-TNF agents have been extensively studied for therapy of inflammatory arthritis as well as osteoarthritis [18,19]. TNF-α enhances expression of MMPs and ADAMTS [8,20,21], and these increased proteases in turn cause exaggerated degradation of cartilage matrix including cartilage oligomeric matrix protein, Col II, and Aggrecan, which promotes progression of OA [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Immunogenicity was reported in patients with available assessment results, and patients were regarded as having a positive ADA status if they tested positive for ADAs at least once up to week 52. Incidence of ADA development was lower with SB4 than with ETN: 1·0% (three of 299) vs. 13·1% (39 of 297), respectively; P < 0·001 . The occurrence, description and severity of ISRs were analysed within subgroups based on the presence of ADAs.…”
mentioning
confidence: 99%
“…At 52 weeks, structural radiological damage was also evaluated using the van der Heijde modified Total Sharpe Score. SB4 and re-ETN had similar results with a score variation from baseline of 0.45 and 0.74 29. In the study extension, of 245 patients who had completed 52 weeks, 126 continued SB4 and 119 switched from re-ETN to SB4 for 48 weeks.…”
Section: Methodsmentioning
confidence: 64%
“…The benefits of SB4 and re-ETN were maintained at 52 weeks of treatment 29. Despite the different response in the ACR70, the EMA concluded that there was sufficient evidence for the biosimilarity relationship 16.…”
Section: Methodsmentioning
confidence: 99%